The Role Of Investigators In Carrying Out Diversion On Children As Perpetrators Of Crimes (Study At The Deli Serdang Police Office) - Palti Habeahan; Rahul Ardian Fikri; Abdul Razak Nasution (International Journal of Society and Law, 2024)
Children as a vulnerable group face unique challenges in the justice system, both as perpetrators and victims of criminal acts. Addressing children involved in criminal offenses requires a balanced approach that prioritizes restorative justice over repressive measures to ensure their development and rehabilitation. This study examines the role of investigators in implementing diversion—a key aspect of restorative justice—at the Deli Serdang Police Station. It explores how diversion helps prevent stigmatization and reduces the negative impact of the judicial process on children. Additionally, the study identifies obstacles encountered by investigators during the implementation of diversion, including institutional and procedural challenges. The findings aim to enhance understanding of the critical role of law enforcement in protecting children’s rights and achieving effective justice.